Online Rating and Reviews of Restaurant on Customer Acquisition - Sharma, Manoj; Pokharel, Yadav Prasad (International Journal of Atharva, 2024)
Online restaurant evaluations have a significant influence on consumer behavior and decision-making processes, as indicated by survey data from Nepal. Important conclusions show that customers’ propensity to visit a restaurant is greatly influenced by the quantity and caliber of reviews, with most respondents placing equal weight on the quantity and recentness of evaluations. This emphasizes how important it is to manage your online reputation to draw in clients. While unfavorable reviews might turn away potential customers, positive ones increase visibility and reliability. Additionally, the survey shows that customers are actively participating—many of them have even gone so far as to actively provide reviews—which suggests that a lively and interactive digital ecosystem is influencing dining preferences.